Survey of Basic Technical Skill for Futsal Male Student High School - Yogi Ferdy Irawan; Indra Prayoto (Jurnal Moderasi Olahraga, 2021)
This research aims to find out: 1) Futsal playing skills of futsal extracurricular participants; 2) Basic techniques of playing futsal extracurricular participants. The sample in this study was an extracurricular futsal participant at Muhammadiyah Vocational School of Sadang which numbered 20 participants. This research design is a quantitative descriptive study with one variable without making comparisons and connecting with other variables. This study uses the FIK Jogja Futsal Skills Test instrument. The data analysis technique used is percentage, aims to collect data, present data and determine value, in addition to conclusions that can be made with reference to the standard of basic futsal skill level that has been determined. The results of the study can be concluded that the level of futsal playing skills of futsal athletes is sufficient with the consideration of the most frequency in the category enough with an average number of 76.61 at intervals 70-82, namely middle value. The results of this study have implications: 1. The emergence of coach awareness in improving the quality of exercises carried out, especially exercises related to the ability to play futsal. 2. Encouraged coach to improve basic technical skills of playing futsal such as passing, dribble and shooting in students, as well as as an effort to achieve maximum results. This research can contribute information about the skill level of futsal athletes, so that it can be used as a consideration in compiling a training program or further research aimed at improving the futsal skills of futsal athletes. Keywords: Basic Skills, Futsal, Extracurricular, Student High School